Choice of fluid for resuscitation of septic shock. Issue 2 (1st March 2002) - Sparrow, A; Hedderley, T; Nadel, S
Abstract : Objectives: To determine current practice in choice of fluid resuscitation in children following publication of a systematic review that demonstrated a higher mortality in patients treated with human albumin solution. Methods: A descriptive telephone and postal questionnaire survey directed at the on call paediatric registrar, lead clinician for paediatrics and the paediatric pharmacist at each of 33 hospitals within the Greater London area. The study was coordinated by the Paediatric Intensive Care Unit at St Mary's Hospital, London. The questionnaire was designed to assess whether a protocol/guidelines existed for resuscitation fluid in children with septic shock; whether the participants were aware of the systematic review and if so, had it changed clinical practice. The word "protocol" was used in its broadest sense to include guideline and policy. Results: 11 hospitals had guidelines for fluid resuscitation of septic shock in children. These varied greatly: only three gave clear instructions of which fluid to use and how to use it. Choice of fluid varied widely and there was wide discrepancy between consultant's and registrar's choice of fluid. The systematic review had lead to a change in policy in two thirds of respondents. Conclusion: It is apparent that few paediatric departments have a written protocol or guidelines for the management of septic shock that is accessible to all those concerned in the acute treatment of seriously ill children. The systematic review into choice of fluid has had an impact on clinical practice with no data regarding whether this is in the patient's best interests.